Model of tacit knowledge transfer in lean management implementation in an organization - Nordin, Norani; Mohamed, Roshidah; Uchihira, Naoshi (IntechOpen, 2020)
The increase in competition worldwide had driven organizations to face with new challenges. The situation had prompted the manufacturers to perform a variety of effective strategies such as the implementation of lean manufacturing system in their organization. In this study, the key elements in developing the lean tacit knowledge transfer within the organization were identified. In addition, this study also investigates the transfer of lean tacit knowledge, which involves the sender and the recipient of lean knowledge within the organization. Data were collected through a single case study for a period of 2 months in an automotive manufacturing plant in Malaysia. The results of the study found that the lean knowledge could be developed through a number of key elements. A model of tacit lean knowledge transfer was developed to help improve work performance during the implementation of lean manufacturing system. In addition, the development of the model can explain how lean knowledge was developed and transferred from one party to another in the organization. The existence of such a model could assist an effective lean manufacturing implementation with every organization should has a good lean knowledge and understand how to properly implement lean in the production process.